Measurement of BCR‐ABL1 by RT‐qPCR in chronic myeloid leukaemia: findings from an International EQA Programme. (14th March 2017) - Scott, Stuart; Travis, Debbie; Whitby, Liam; Bainbridge, John; Cross, Nicholas C. P.; Barnett, David
Summary: Sequential measurement of BCR‐ABL1 mRNA levels by reverse transcription quantitative polymerase chain reaction (RT‐qPCR) is embedded in the management of patients with chronic myeloid leukaemia (CML), and has played an important role in the remarkable improvement in patient outcomes seen in this disease. As a provider of external quality assessment (EQA) in this area, UK NEQAS for Leucocyte Immunophenotyping (UKNEQAS LI) has a unique perspective on the changing face of BCR‐ABL1 testing in CML. To assess the impact of technical standardisation and the development of the International Scale (IS) upon the accuracy of BCR‐ABL1 testing, we reviewed EQA trial data from 2007 to 2015. Comparison of participant results identified considerable variability at both high and low levels of disease, including therapeutically important decision points; however, results converted to the IS showed less variability compared to unconverted data sets. We also found that different methods of converting to the IS produce consistently different median results within UKNEQAS LI IS data sets. This data suggests that whilst the development of the IS has improved the comparability of results between centres, there is still the need for further improvement in the processes of converting raw results to the IS in order to fully realise the benefits of molecular monitoring of CML.